The Impact of the Colombian Framework for English (COFE) Project : An Insiders'Perspective (2000)
ABSTRACT: Under the influence of the COFE Project, the ultimate goal of which was to improve the teaching of English in secondary schools in Colombia, English teacher training courses underwent profound changes, which prepared the ground for curricular adjustments required by the Comité Nacional de Acreditacion. The article presents the results of the evaluation of the Cofe project conducted by a team of teachers from nine universities from five areas: language development, professional development, research, resources and evaluation.